A prospective study of the impact of an emotional intelligence program on opioid relapse and its determinants in upper Egypt - Hanan Faried Maghawry; Alaa M. Darwish; Naglaa Abd Elmeged Mohammed; Nadia Abd El-ghany Abd El-hameed; Gellan K. Ahmed (BMC Psychology)
Abstract Background Opioid use is a growing concern worldwide with high relapse rates and psychiatric comorbidities. Emotional intelligence (EI) has been associated with positive health outcomes, yet limited research exists on EI-based interventions for opioid use disorders. The study aimed to assess EI levels among individuals with opioid addiction and implement an EI program to reduce addiction severity and relapse rates, as well as examine potential factors that contribute to enhancing EI. Methods A quasi-experimental study assigned 40 males with opioid use disorder into an intervention group receiving a 2-week EI program (n = 20) and a control group (n = 20). Healthy comparison group (without opioid use disorder) (n = 20) was also included. Measures including the Emotional Intelligence Scale, Personality Inventory for DSM-5, Symptom Checklist-90-Revised (SCL-90-R), Addiction Severity Index, and Advance Warning of Relapse (AWARE) questionnaire were used to assess the groups at baseline,2 weeks and 3-month follow-up in patients with opioid use disorder. Results The healthy group exhibited lower scores on disinhibited personality subscales, maladaptive personality traits, and SCL-90-R subscales than the opioid addiction groups at baseline. The EI intervention group displayed substantial increases in EI subscale scores at the second and third follow-up assessments compared to the control group. At AWARE scale follow-up, all control group patients had relapsed, versus only one patient in the EI intervention group. Conclusions Participants with opioid addiction demonstrated lower baseline EI and higher rates of psychiatric symptoms and maladaptive personality traits than healthy group. A brief EI intervention led to significant EI increases and lower relapse rate versus standard treatment alone.